The performance of the cinnamon tree and the cross in the hispanic-mapuche interethnic relationships during the 17 th Century. A case of Cannibal logic or historical register? - Larach, Pablo (Cuadernos de Historia, 2023)
Taking into account the similarities expressed on the use given by Hispanics and Mapuche alike to the cross and the cinnamon tree during the peace parliamentary meetings and their armed encounters during the 17 th Century, we state that the symbol of the cross was striped out by the mapuche of the free lands of the religious protective aura given by the missionaries, and dressed with a protective aura, meant not to defend them from those supernatural beings which populated the surrounding nature, but as a political symbol that stated the quality as Indian friend or allied to the Spaniard of all those who signed the peace treaties at the parliaments. In this sense, its use is seen as a performance act intended to represent themselves historically within the context of Hispanic-Mapuche relationships.